ETHYLENE IN SEED PHYSIOLOGICALQUALITY: A REVIEW (REMUNOM, 2026)
Ethylene plays a central role in regulating seed dormancy, germination, and vigor, acting as a strategic modulator of the interaction between hormonal pathways and redox signals. This review aimed to integrate recent evidence on the biosynthesis and signaling of ethylene with abscisic acid (ABA), gibberellins (GAs), and reactive oxygen species (ROS), and their implications for the physiological quality of seeds. The analyzed literature demonstrates that ethylene influences the transition from quiescence to active growth through the modulation of hormonal sensitivity, metabolic activation during imbibition, and controlled weakening of seed covering tissues. Functional antagonism with ABA and cooperation with GAs constitute a determining regulatory axis for overcoming dormancy, while integration with the redox state contributes to the fine-tuning of germination under variable environmental conditions. Evidence also indicates that responsiveness to ethylene can influence parameters associated with vigor, such as germination speed and uniformity, as well as tolerance to abiotic stresses. However, gaps remain regarding interspecies variability in ethylene sensitivity, the dynamics of ACC homeostasis during storage, and the role of this hormone in seeds subjected to aging. It is concluded that ethylene should be understood as a component of an adaptive regulatory network that integrates hormonal, metabolic, and environmental signals, representing a promising target for advances in seed science and technology.